Identification, Characterization, and X-ray Crystallographic Analysis of a Novel Type of Lectin AJLec from the Sea Anemone Anthopleura japonica - Unno, Hideaki (Sci Rep, 2018)
A novel galactose-specific lectin, AJLec (18.5 kDa), was isolated from the sea anemone, Anthopleura japonica. AJLec was characterized using the hemagglutination assay, isothermal titration calorimetry (ITC), and glycoconjugate microarray analysis and we found that AJLec has a specificity for galactose monomers and β-linked terminal galactose residues in complex carbohydrates, but not for N-acetylgalactosamine (GalNAc), which is commonly recognized by galactose-binding lectins. The primary structure of AJLec did not show homology with known lectins, and a crystal structural analysis also revealed a unique homodimeric structure. The crystal structure of AJLec complexed with lactose was solved by measuring the sulfur single-wavelength anomalous diffraction (S-SAD) phasing with an in-house Cu Kα source method. This analysis revealed that the galactose residue in lactose was recognized via its O2, O3, and O4 hydroxyl groups and ring oxygen by calcium coordination and two hydrogen bonds with residues in the carbohydrate-binding site, which demonstrated strict specificity for the β-linked terminal galactose in this lectin.